Analysis of Public Perception on the Implementation of Waste Management Policies in Major Indonesian Cities Based on Environmental Awareness and Social Participation - Rahman, Andi (Moccasin Journal De Public Perspective, 2024)
This study analyzes public perception of waste management policies in major Indonesian cities, focusing on the influence of environmental awareness and social participation. Using a quantitative research method, data were collected from 400 urban residents in Jakarta, Surabaya, Bandung, and Makassar through structured surveys. The results indicate that public perception of waste management policies is generally moderate, with Surabaya showing the highest satisfaction levels. A significant positive correlation was found between environmental awareness and public perception, suggesting that individuals with greater environmental knowledge tend to view waste management policies more favorably. Furthermore, social participation plays a critical role in enhancing policy effectiveness, as cities with higher levels of community engagement, such as Surabaya and Makassar, reported better outcomes. The findings highlight the need for improved environmental education and the promotion of community-based waste management programs to foster greater public engagement and support for sustainable waste management practices. These insights can inform policymakers in refining waste management strategies and increasing public participation.